PENGGUNAAN SURFAKTAN UNTUK MENGURANGI KANDUNGAN AIR DALAM EMULSI MINYAK - Ade Syafrinaldi (Badan Pengkajian dan Penerapan Teknologi, 2017)
Emulsified oil is considered as rarely acceptable waste oil to be reused or even recycled. Efforts thathave been made in the last 40 years for the development of reliable and efficient demulsificationtechniques, cannot avoid the hard fact that it is not an easy task to break the most emulsified oil in shorttimes. For economic and operational reasons, it is necessary to separate the water from the emulsifiedoil to an acceptable level before it fed into the reclaimed fuel oil plant. One of the most widely usedmethods in treating water-in-oil emulsions is using surfactant to accelerate the emulsion breakingprocess. Three commonly used surfactants with high HLB value (Nonyl Phenol Ethoxylate NP-9,Tween 80 and Sodium Dodecyl Sulphate SDS), dissolved in toluene to form 25% solution, wereapplied into 100 ml emulsified waste lubricants originated from collectors in Balikpapan suburb. Thedemulsifying effects of all three surfactants were then examined, including the heat effect by warmingup the whole system. All experiments were carried out in different concentrations of each solution, 500ppm, 700 ppm, 900 ppm and 1100 ppm. The performance level was determined by the amount of waterseparated. The experiments continued using best performed surfactants and centrifugal separators tomeet the targetted water content in the waste lubricants by 5% and sediment content by 3% before itfed into the reclaimed fuel oil plant. Result showed that surfactants with the best demulsifying effectwere NP-9 and SDS. Both worked at the optimum concentration of 700 ppm. The targetted watercontent was successfully exceeded. Water content in the waste lubricants was reduced from 34% to0.08% with NP-9 and to 0.8% with SDS. Sediment content was however not as successful. Sedimentcontent in waste oil was reduced from 12.30% to only 6.56% with NP-9 and to only 5.11% with SDS.The removed water from the process needs further treatment before disposal. The concentration ofBOD 5, COD, oil and fat, and ammonia are beyond the quality standard of waste water. The wastewater passed only in pH, Dissolved Sulfide and Total Phenol.Keywords : surfactant, emulsion, demulsification effect, demulsifier solution, hydrophilic lipophilicbalance